Induction of endoplasmic reticulum stress markers in an acromegaly model. Issue 9 (23rd June 2022) - Elbialy, Abdalla; Sulidan, Kaidiliayi; Bhuiyan, Afsana; Igarashi, Yoji; Yoshitake, Kazutoshi; Yamanouchi, Dai; Kang, Junsu; Asakawa, Shuichi; Watabe, Shugo; Kinoshita, Shigeharu
Abstract: Acromegaly is a growth hormone (GH) excess pathological condition in humans. Acromegaly is associated with somatic disfigurement and a wide range of systemic manifestations such as arthritis, neuropathy, carpal tunnel syndrome, reproductive disorders, metabolic disorders, and gastrointestinal complications. The influence of excess GH on the cellular level could aid in understanding the root causes of acromegaly‐related health complications. Previously, we found that GH excess induces DNA damage to somatic cells and reduces the stem cells number and causes premature aging. In this study, an in‐depth analysis of the acromegaly RNAseq data revealed the disruption of important biological cellular processes. Gene set enrichment analysis, heatmap, and enrichment analysis of acromegaly RNAseq data revealed induction of endoplasmic reticulum (ER) stress markers in various organs. Interestingly, the induction of ER stress was even more apparent than in aged zebrafish. Splicing of box‐binding protein‐1 (XBP1) mRNA is a hallmark of ER stress. Therefore, we quantified spliced XBP1 mRNA in different organs of our acromegaly model. Thus, our study emphasizes the importance of ER stress in GH oversecretion, which is important for understanding the health complications of acromegaly.